Training finnish morphology with a smartphone application in adult beginner level learners - Salmela, Rosa; Lehtonen, Minna; Köykkä, Johanna; Garusi, Stefano; Laine, Matti; Bertram, Raymond (Taylor & Francis, 2025)
The rich inflectional grammar of Finnish is often considered a challenge for second language (L2) learners. However, the inflectional variation is based on relatively systematic morphological and morphophonological rules. Smartphone applications could offer an effective way to train these rules by utilizing adaptive spaced repetition exercises. Currently there is little research on morphology learning via Mobile Assisted Language Learning (MALL) applications in morphologically rich languages. The present study introduces a newly developed Finnish Morphology Application (FMA) that aims to teach beginner-level Finnish morphology. In a randomized controlled trial, the test group participants (n = 33) practiced Finnish morphology with the FMA during a three-week period, and their improvements were compared to those of an active control group using a general Finnish language learning application (n = 38). The practiced morphological operations comprised transparent and semi-transparent inflections. Pre- and posttests included a visual lexical decision task and a morphological production task. In comparison to the control group, the FMA group improved substantially in written morphological production skills, especially in transparent inflections. In visual lexical decision task, there was an improvement in accuracy for trained words in the FMA group, but this improvement applied to both transparent and semi-transparent inflections as well as monomorphemic nouns. In reaction times, there were no differences between the groups. Self-ratings of perceived efficacy of the FMA regarding grammar and vocabulary varied from neutral to positive. The results suggest that the FMA is particularly useful for learning inflectional production skills in Finnish by adult beginner level learners but can also be used to train word recognition.